Impacts of oral health on life quality metrics: correlations with job function, psychological well-being, self-perception, and dietary behavior - Helmi, Mohammad (Frontiers in Oral Health, 2025)
IntroductionThis study evaluates the impact of oral health issues on critical areas of daily functioning, including job performance, psychological well-being, self-rated oral health, and dietary habits.MethodsUtilizing NHANES data, the analysis applies Pearson correlation, multiple regression, and data visualization techniques (scatter plots, heatmaps, and box plots) to quantify associations between oral health variables, such as mouth aching (OHQ620), food avoidance (OHQ660), job difficulty due to mouth issues (OHQ640), and embarrassment (OHQ680).ResultsStrong correlations were found between mouth aching and job difficulty due to mouth issues, with a Pearson correlation coefficient of 0.99, and between difficulty eating (OHQ670) and job difficulty due to mouth issues, with a coefficient of 0.98. Psychological impacts were also notable; feeling bad about one's mouth (OHQ630) had a high correlation with embarrassment (0.99), while mouth aching had a weaker association (0.88). Self-rated oral health (OHQ845) showed a negative correlation with both mouth aching (−0.83) and feeling bad about one's mouth (−0.83), indicating decreased self-assessment of oral health as symptoms increase. Multiple regression revealed that difficulty eating had a substantial positive coefficient (1.19) for food avoidance, while mouth aching had a minor negative effect (−0.13). Smoking exposure was positively associated with oral health issues, particularly with mouth aching and embarrassment.ConclusionsThe findings highlight significant impacts of oral health issues on job performance, psychological well-being, and lifestyle, suggesting the need for integrated oral healthcare strategies that address both physical discomfort and emotional consequences.Practical implicationsEnhanced oral health interventions focusing on symptom management and psychological support could reduce nutrition barriers, improve occupational functioning, and increase quality of life.